TECHNOLOGY OF REPAIR OF PARTS OF AGRICULTURAL MACHINES, EQUIPMENT WITH COMPOSITE MATERIALS (Conference Zone, 2022)
This article provides information on the technology for the restoration of worn parts during the operation of agricultural machinery and equipment, on the example of the processes of changing the working surface of tillage units, the technology for the restoration of a new powder composite material by resistance welding.